(untitled) (Revista Brasileira Multidisciplinar, 2024)
Being on the streets exposes trans people to extreme vulnerability and risk. Regarding trans women, in addition to aggravating the vulnerability already exposed on the streets, the main obstacle in the use of health services is discriminatory assistance, structured on institutionalized transphobia and hostility in services. The objective of the study was to analyze the perception of trans women living on the streets regarding the use of health services. A descriptive qualitative study was carried out from August 22 to September 21, 2021, the scenario for the research was the Integrated Center for Assistance to Women and there was the participation of four trans women living on the streets. The collection was carried out through semi-structured interviews and the data were submitted to content analysis. After reading the material, it was possible to identify three categories: I) Health knowledge; II) Facilities and difficulties in the use of health services by trans women; III) Planning for the future. Trans women living on the streets are subject to doubly vulnerable, due to the context in which they are inserted. The results allow confirming the relevance of training professionals to serve the trans public, as well as the need to produce new studies that address the theme.